Implementation of Multiliteracy in Elementary School - Putri, Rahma Eka; Damayanti, Vismaia S (International Conference on Elementary Education, 2024)
The implementation of the Merdeka curriculum aims to give teachers the freedom to create quality learning which can be adapted to the needs and learning environment of their students. This is in line with the implementation of multiliteracy because it answers the challenges of 21st century skills, where 21st century skills require balanced knowledge and skills. as the basis for quality human resources in an era that is always developing. This research is motivated by the students' ability to master technology and language literacy, especially regarding reading and writing critically and creatively when learning Indonesian. This is important to pay attention to because if students still lack mastery of technology and language literacy then the application of multiliteracy will be difficult and 21st century skills will not be achieved and this will result in poor quality human resources. This research aims to find out and describe how the implementation of multiliteracy in elementary schools is going well or vice versa, and see what factors support whether or not the implementation of multiliteracy in elementary schools is implemented. The research method used is a descriptive qualitative approach by collecting data through observation, interviews and documentation. Meanwhile, data analysis uses data reduction techniques, data presentation, and drawing conclusions. Based on the research results, it can be concluded that the application of multiliteracy in elementary schools is very important for students, even though it has not been implemented optimally, teachers always try to make the application of multiliteracy better than before. Supporting factors for the implementation of multiliteracy to run well are teacher ability, student interest in learning, and adequate facilities.